RISK MANAGEMENT OF STATE REGULATION PROJECTS FOR THE INNOVATION CLUSTERS DEVELOPMENT - Olga Orlova-Kurilova (Економічний часопис Східноєвропейського національного університету імені Лесі Українки, 2020)
Abstract. Clustering initiates innovative activity in all phases of reproduction by reducing barriers to market entry and transaction costs for information seeking, creating the conditions for attracting additional financial resources, and generating demand for highly qualified personnel. In this regard, it is particularly important to ensure the effective functioning and development of innovative clusters in the country through the development and implementation of projects for their state regulation. The theoretical aspects of realization of projects for state regulation of innovative clusters development are considered in the article. The model of risk management of government regulation projects for the innovative clusters development is schematically presented. An algorithm for selection of state regulation projects is proposed, which will facilitate the selection of optimal projects from the set of available projects for implementation, as well as the selection and determination of the most appropriate places for their application.